A Comparison of the Movements of the Rear Parts of Dolphins and Butterfly Swimmers - Ungerechts, B. (Biomechanics and Medicine in Swimming, 1983)
The locomotion of dolphins attracts attention in some respects, as it is harmonic and results in very high swimming speeds. The adaptation of this movement in a competitive swimming stroke for humans such as he butterfly stroke is therefore plausible. The body movements of the rear parts of both dolphins and butterfly swimmers, respectively, result in the production of drag and thrust in a unique situation. Whereas the dolphin's tail and fluke movements result solely in a powerful thrust, the effect of a swimmer's dolphin kick is discussed with more controversy. Barthels and Adrian (1975) suggested that the down-beat contributes to the propulsion of the body. Makarenko (1978) claimed that the dolphin kick sometimes has a propulsive effect and that in some swimmers, leg movements stabilize the body by elevating the hips. Jensen and Mcllwain (1979) demonstrated, on the basis of an estimate for joint reaction forces, that the first kick may accelerate the swimmer and elevate the hips. The joint reaction was calculated on the assumption that the production of propulsive forces depends on surface area, angular velocity of the body part considered, density of water, and drag coefficient. In this approach, the forces due to the interaction of the whole body and the water are treated as if every part of the body is counteracted by resistive forces. Therefore, this concept was called a "resistive model."